The changing nature of return migration to Afghanistan - Kuschminder, K; Siegel, M; Majidi, N (Refugee Studies Centre, University of Oxford, 2014)
Donors and practitioners need to adapt to a changing landscape of migration and return migration in their efforts to target Afghans most in need of assistance.